Investigating population-level immunosenescence: From bench to bedside - Cunha, Lucas Leite; Valsecchi, Victor Alexandre dos Santos; Ward, Laura Sterian (Frontiers in Immunology, 2022)
The immune response is remodeled with aging in a process called immunosenescence. Some immunologists conceive immunosenescence as an adaptation of immunity to the aged immune-environment rather than a merely collapsed reactivity of immune cells against microbes and tumor cells. Others believe on an uninterrupted activation of the innate immune system with aging, leading to a low grade, sterile and chronic proinflammatory state called inflammaging. For instance, it is possible that chronic infection by cytomegalovirus leads to persistent production of viral load. This phenomenon offers periodic stimuli to the immune system that ultimately contribute to the remodeling of the immune response. If investigating immunosenescence at the cellular level is already a difficult task, considering the population level is much more complex. However, by studying immunosenescence at the population level, we can extract valuable results with viable applications. While studies with animal models allow scientists to deepen their understanding of the mechanisms of immunosenescence, studying large populations can bring practical innovations to medicine and the health system. Many researchers and funders have dedicated themselves to producing methods for the evaluation of immunosenescence on a large scale, aiming to elucidate new mechanisms by which diseases are established in the elderly. The description of how the immune response is remodeled with aging emerges as a new tool to identify the subset of subjects in which unhealthy aging is a matter of time, to help better individualize clinical management and select patients who may benefit. of early interventions. This review focuses on functional assays as valuable methods for measuring the remodeling of the immune response with aging and discuss their clinical impact. We also recall fundamental concepts for understanding the aging process of the immune response. In addition, we highlight future prospects for immunosenescence research.